The c-Myc/TBX3 Axis Promotes Cellular Transformation of Sarcoma-Initiating Cells - Damerell, Victoria; Ambele, Melvin Anyasi; Salisbury, Shanel; Neumann-Mufweba, Alexis; Durandt, Chrisna; Pepper, Michael Sean; Prince, Sharon (Frontiers in Oncology, 2022)
Sarcomas are highly aggressive cancers of mesenchymal origin whose clinical management is highly complex. This is partly due to a lack of understanding of the molecular mechanisms underpinning the transformation of mesenchymal stromal/stem cells (MSCs) which are presumed to be the sarcoma-initiating cells. c-Myc is amplified/overexpressed in a range of sarcomas where it has an established oncogenic role and there is evidence that it contributes to the malignant transformation of MSCs. T-box transcription factor 3 (TBX3) is upregulated by c-Myc in a host of sarcoma subtypes where it promotes proliferation, tumor formation, migration, and invasion. This study investigated whether TBX3 is a c-Myc target in human MSCs (hMSCs) and whether overexpressing TBX3 in hMSCs can phenocopy c-Myc overexpression to promote malignant transformation. Using siRNA, qRT-PCR, luciferase reporter and chromatin-immunoprecipitation assays, we show that c-Myc binds and directly activates TBX3 transcription in hMSCs at a conserved E-box motif. When hMSCs were engineered to stably overexpress TBX3 using lentiviral gene transfer and the resulting cells characterised in 2D and 3D, the overexpression of TBX3 was shown to promote self-renewal, bypass senescence, and enhance proliferation which corresponded with increased levels of cell cycle progression markers (cyclin A, cyclin B1, CDK2) and downregulation of the p14ARF/MDM2/p53 tumor suppressor pathway. Furthermore, TBX3 promoted the migratory and invasive ability of MSCs which associated with increased levels of markers of migration (Vimentin, SLUG, SNAIL, TWIST-1) and invasion (MMP2, MMP9). Transcriptomic analysis revealed that genes upregulated upon TBX3 overexpression overlapped with c-myc targets, were involved in cell cycle progression, and were associated with sarcomagenesis. Together the data described indicate that the c-Myc/TBX3 oncogenic molecular pathway may be a key mechanism that transforms hMSCs into sarcomas.